Palpation and dorsal acetabular rim radiographic view for early detection of canine hip dysplasia - Charette, B.; Dupuis, J.; Beauregard, G.; Breton, L.; Paré, J. (Veterinary and Comparative Orthopaedics and Traumatology, 2001)
The objectives of this study were to standardize a palpation technique and to determine within and between examiners, the repeatability in interpreting the angle of reduction, subluxation and the acetabular slope measurements. Also it was desired to ascertain the effect of pelvis positioning on the acetabular slope measurement on sixmonth- old dogs. On palpation examination fifty-three (53) dogs had their angles of reduction and subluxation measured. A radiographic examination including a standard hip-extended view, a compression and a distraction view and a dorsal acetabular rim view were performed on each dog.The within examiner repeatability was excellent for both the angle of reduction and subluxation (r = 0.975, p = 0.82 and r = 0.977, p = 0.81 respectively). The between examiners repeatability was good for the angle of reduction (r = 0.843, p = 0.51) but only a fair correlation was found for the angle of subluxation (r = 0.652, p = 0.83). For the acetabular slope measurement, an excellent within examiner correlation was observed (r = 0.940, p = 0.52). However, though a good correlation was found between examiners, a significant difference was found in the measurements of the three examiners (r = 0.780, p < 0.0001). The under- or overrotation position slightly changed the slope measurement but a fair correlation was still observed with the perfect position (r = 0.769, p = 0.074 and r = 0.684, p = 0.061 respectively). If the pelvis is turned to one side, a correlation was not found (r = 0.090, p = 0.847). The high repeatability of the angle of reduction measurement in six-month-old dogs suggests that it may be used by multiple examiners, with the expectation of comparable and consistent results. The modified method of the acetabular slope measurement improved the correlation, but a significant difference was still observed between examiners.Early detection in life of canine hip dysplasia is important. The angle of reduction and the acetabular slope have been evaluated as diagnostic tools. With regard to its repeatability between examiners, the use of the angle of reduction by multiple examiners will be acceptable. The correlation between examiners in the acetabular slope measurement was good but a significant difference was present. Part two is now being analyzed.
Keywords: Hip dysplasia; young dogs; acetabular slope; angle of reduction; angle of subluxation